Hypoglycemia in athletes with diabetes - Kirk, S. E. (Clinics in Sports Medicine, 2009)
For many years, one of the mainstays of therapy for patients with either type 1 or type 2 diabetes has been exercise, balanced with medical nutrition therapy and medications. A key limitation to achieving this balance has been the increased risk of hypoglycemia, including that induced by increased glucose use brought about by exercise or athletic activity. This review focuses primarily on type 1 diabetes and athletic activity; however, many of the principles discussed below apply to type 2 diabetes as well.